PRODUCTION OF RECOMBINANT, NON-TAGGED PHENYLALANINE AMMONIA-LYASES EMPLOYING TEV PROTEASE-REMOVABLE AFFINITY TAGS - FILIP, Alina; BATA, Zsófia; ANGHEL, Anca Elena; POPPE, László; BENCZE, László Csaba (Studia Universitatis Babeș-Bolyai Chemia, 2022)
Nowadays, protein purification by the aid of affinity tags can be carried out with high speed and efficiency. However, in several cases, affinity tags can significantly alter the key properties of enzymes, especially activity and/or thermostability. This study focused on the purification of the non-tagged phenylalanine ammonia-lyase from Petroselinum crispum (PcPAL), as well as on the purification of the TEV (Tobacco Etch Virus) protease, the molecular scissors used to remove the affinity tag from the recombinantly expressed PcPAL. Removal of the 6xHis-tag led to a 1.5-fold increase in the specific activity of PcPAL, while the absence of the affinity tag did not significantly alter the thermostability of the protein. The purity and oligomerization state of the proteins of interest were also analyzed by size exclusion chromatography, both before and after the removal of the affinity tag, confirming the stability of the tetrameric fold of PcPAL.